The Mediating Role of Attitude in the Relationship Between the Extrinsic and Intrinsic Attributes of Japanese Frozen Foods and Consumers’ Intention to Purchase Them: Evidence from Malaysia - Omar, Nor Asiah; Lahath, Aishath; Astuti, Rifelly Dewi; Jamaludin, Nurul Atasha; Alam, Syed Shah (UI Scholars Hub, 2023)
Research Aims: To examine the intrinsic and extrinsic factors affecting consumers’ attitudes toward Japanese-made frozen foods and, hence, consumers’ purchasing behaviour. Design/Methodology/Approach: Consumers who were aware of Japanese-made frozen foods were the sample chosen. Convenience sampling plus a cross-sectional, self-administered online survey questionnaire collected data from 307 participants. Research Findings: Findings showed that brand reputation, halal label, convenience, and food quality were positively related to attitude towards Japanese frozen food, whereas health consciousness was negatively associated with attitude. Attitudes toward Japanese frozen foods were found to mediate relationships between brand reputation and purchase intention, halal label and purchase intention, and food quality and purchase intention of the foods. Theoretical Contribution/Originality: Given the fierce competition and growth within the frozen food industry, this study advanced the knowledge of Malaysian consumer purchasing behaviour in the context of Japanese frozen foods. Managerial Implication in the South East Asian Context: The mediating role of attitude toward Japanese frozen foods in the relationship between extrinsic and intrinsic product factors and purchase intention among consumers in Malaysia provided valuable insights on foods exported from a predominantly non-Muslim country to a predominantly Muslim country in South East Asia. Research Limitation & Implications: The scope of this study was limited to Malaysians who were aware of Japanese frozen foods. Examining the extrinsic and intrinsic attributes of the foods was crucial because the awareness of and preference for Japanese frozen foods is still low in Malaysia, and there is limited knowledge about the products.